Fatores associados ao presenteísmo em trabalhadores de enfermagem - Santos, Bruno da Silva (2020)
Introduction: Nursing work presents itself as an exhausting work activity in the hospital sectors, mainly due to its specificity related to human care. The environments in which these professionals exercise their functions can cause these professionals to become ill, which in most cases will interfere with the quality of care offered to the patient. Such afflictions can lead these workers to present conditions, which is characterized by the presence of the professional at his workplace, even if he feels sick, whether physically or psychologically. It is observed that presenteeism has as main outcome the loss of productivity - both in quantity related to physical and mental performance, as well as in quality when it comes to increasing the possibilities of errors. Objectives: to analyze the factors associated with presenteeism in nursing workers regarding socio-demographic variables, health and work conditions, productivity and musculoskeletal symptoms. Materials and Method: This is a cross-sectional, correlational and analytical study, with 306 nursing workers from a hospital and municipal emergency room in a capital city in the Midwest of Brazil. Data were collected using four self-administered instruments: Stanford Presenteeism Scale, Work Limitations Questionnaire, Nordic Musculoskeletal Questionnaire and socio-demographic questionnaire on health and work conditions of nursing professionals. The study variables were tested with presenteeism by means of bivariate and multivariate analyzes, respecting a confidence interval of 95% estimates. All ethical prerogatives were followed. Results: The 306 professionals in the study were represented by 86 nurses (28.1%) and 220 nursing technicians (71.9%), with presenteeism observed in 43.8% of nursing professionals, with significant associations with the type hiring (p=0.002), professionals working in intensive care units (p=0.008) and musculoskeletal symptoms, with low back pain being the main among them (p=0.001). Productivity was decreased by 8.8%, with the global WLQ Index score = 0.08 among present workers, and the physical demand domain was the most affected, represented by an average of 40.8 when work limitations were assessed, with significant association of presenteeism with that domain (p<0.0001). Conclusion: the study confirms the association of presenteeism with the fall in productivity, allowing a greater understanding of the phenomenon, in order to think about actions that can subsidize better working conditions, quality of life, health and work for nursing professionals.